Educational Games on Creative Thinking Skills and Chinese Language Learning Achievement in Vocational Schools - Yue fang LIN; I Komang Sudarma; Ketut Agustini (Jurnal Media dan Teknologi Pendidikan, 2025)
Against the backdrop of global educational game development and vocational education reform in China, Chinese language instruction in vocational secondary schools remains dominated by traditional lecturing, provides limited support for creative thinking, and is insufficiently aligned with Generation Z’s digital learning characteristics. Moreover, research on the integration of educational games in vocational Chinese language learning is still limited and fragmented, making this study both necessary and timely. This study adopted a quasi-experimental design (200 students, 100 each in the experimental group and the control group) to explore the impact of educational games on vocational secondary school students’ creative thinking and Chinese language achievement. The experimental group adopted a game-integrated teaching model, while the control group used traditional teaching methods.The research results showed that: the creative thinking score of the experimental group increased by 30.2% (t=10.35-11.76, p<0.001), and the Chinese language achievement increased by 28.0% (t=9.76-12.45, p<0.001); the improvement of the control group was minimal. There was a significant positive correlation between the two (r=0.69, p<0.001), and learning motivation and strategies played a mediating role (β=0.22-0.32, p<0.001). Educational games can significantly promote the development of vocational school students' creative thinking and can effectively improve vocational school students' Chinese language achievement.